2001
DOI: 10.5858/2001-125-0127-uobcci
|View full text |Cite
|
Sign up to set email alerts
|

Use of Buccal Cells Collected in Mouthwash as a Source of DNA for Clinical Testing

Abstract: Context.—To maximize the participation rate in population genetic studies, alternatives to invasive whole blood collection are increasing. One such alternative is buccal epithelial cell collection, which, in contrast to venipuncture and finger sticks, is painless. Buccal cells, if collected and purified efficiently, offer an acceptable source for DNA to be used in research and clinical applications. Objective.—To develop a noninvasive sampling method for collecting cells for routine DNA testing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(9 citation statements)
references
References 10 publications
1
7
0
1
Order By: Relevance
“…Our results suggest that samples collected by Scope mouthwash are generally stable for most microbial metrics, but there was higher abundance of the phylum Firmicutes and lower Proteobacteria after 4 days at room temperature. Similar to our results, samples collected with mouthwash in previous studies found microbial composition was stable for 4 days and 1–2 weeks variable lengths of time [ 7 , 22 , 23 ]. One study also found an increase in relative abundance of Firmicutes and a decrease in Bacteroidetes, Proteobacteria, and Fusobacteria after 4 days at room temperature with Scope mouthwash samples [ 7 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our results suggest that samples collected by Scope mouthwash are generally stable for most microbial metrics, but there was higher abundance of the phylum Firmicutes and lower Proteobacteria after 4 days at room temperature. Similar to our results, samples collected with mouthwash in previous studies found microbial composition was stable for 4 days and 1–2 weeks variable lengths of time [ 7 , 22 , 23 ]. One study also found an increase in relative abundance of Firmicutes and a decrease in Bacteroidetes, Proteobacteria, and Fusobacteria after 4 days at room temperature with Scope mouthwash samples [ 7 ].…”
Section: Discussionsupporting
confidence: 92%
“…DNA was collected in mouthwash (Heath et al, 2001) and extracted using the standard phenol-chloroform method. DNA concentrations were determined using a NanoDrop ND-1000 Spectrophotometer (ThermoFisher Scientific, Waltham, MA) and standardized to 10 ng/µL for the polymerase-chain-reaction (PCR) protocol.…”
Section: Genotyping Of Ar Cag Repeat Polymorphismmentioning
confidence: 99%
“…Various authors report that saliva samples obtained after the use of mouthwash can be stored at room temperature for 1-2 weeks without affecting the quality or quantity of DNA. 17,18,24,25 In the present study, we found that the samples stored at room temperature in Mexico City (20-24 8C) could be maintained stable and viable for up to 30 days. Although the DNA concentration was sharply reduced during this period, the quality and quantity of genomic DNA were still in optimal conditions for performing genotyping and sequencing.…”
Section: Discussionmentioning
confidence: 47%